PENGARUH MEDIA BANDICAM BERBASIS PEMBELAJARAN BERMAKNA TERHADAP HASIL BELAJAR TEKS BIOGRAFI SISWA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the relatively low student learning outcomes in understanding biographical texts, which were influenced by the limited use of interactive learning media and the dominance of conventional teaching methods. The purpose of this study was to examine the effect of using Bandicam media integrated with a meaningful learning approach on students’ learning outcomes in biographical text material. This research employed a quantitative approach with a quasi-experimental design using the One Group Pretest–Posttest Design. The participants consisted of 18 students from class X.3 at MA Syekh Yusuf, Gowa Regency. Data were collected through pretest and posttest assessments, as well as observations of student activities during the learning process. The data were analyzed using both descriptive and inferential statistics, including the paired sample t-test and N-Gain analysis. The findings revealed an improvement in students’ learning outcomes after the implementation of Bandicam-based meaningful learning, as indicated by higher posttest scores compared to pretest scores. Furthermore, the statistical test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between students’ performance before and after the treatment. In addition, the N-Gain results demonstrated that the improvement fell into the moderate to high category. Therefore, it can be concluded that the use of Bandicam media combined with a meaningful learning approach has a significant effect on enhancing students’ learning outcomes in biographical text material.